Respuesta :
Answer:
[tex]let \: the \: numbers \: be \: x \: and \: y \\ then \\ [/tex]
[tex]x + y = 201(equation \: 1) \\ x - y = 69(equation \: 2)[/tex]
According to 2nd equation
[tex]x = 69 + y[/tex]
Putting the value of x in the first equation
[tex]69 + y + y = 201 \\ \implies \: 69 + 2y = 201 \\ \implies \: 2y = 201 - 69 \\ \implies \: y = \frac{132}{2} [/tex]
[tex] \implies \: y = 66[/tex]
We know that
[tex]x = y + 69 \\ \implies \: x = 66 + 69 \\ \implies \: x = 135[/tex]
If you have any doubts you can comment and ask
Answer:
135 and 66
Step-by-step explanation:
Solve the system of equations
Equation 1: x + y = 201
Equation 2: x - y = 69